ENGLISH MAJOR STUDENTS’ PERCEPTIONS TOWARDS WATCHING ENGLISH MOVIES IN LISTENING AND SPEAKING SKILLS DEVELOPMENT - Liando, Nihta Vera; Sahetapy, Ray Jusuf; Maru, Mister Gidion (Advances in Social Sciences Research Journal, 2018)
The aim of the study was to find out English major students’ perceptions towards watching English movies to develop listening skill and speaking skill. This study was conducted at one university in North Sulawesi, specifically on the students who took Listening and Speaking class. The instrument used in the data collection was a questionnaire that consists of three parts for finding out the background of the respondents, English movie watching perceptions, and level agreement towards English movies. The data were analyzed using Microsoft Excel and shown in tables of frequency, percentage and mean. The findings indicated that English major students are aware that they can improve their listening skill by watching English movies. Subtitles also can help respondents to understand conversation in the movies, and English movies are believed to be more effective than other media as teaching tools. English major students also believe that they can improve their speaking skill by watching English movies. Students think watching English movies has more direct influence to listening skill compared to speaking skill. Future studies are recommended to conduct interviews of students to gain more information or arrange a test of student listening and speaking skills. Other interesting topics would be to study further about whether English subtitles or Indonesian subtitles is more effective as learning media, and also which movie genre is more effective in English skills development.